2007
DOI: 10.1353/etc.2007.0001
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of One-to-One Embedded Instruction in the General Education Classroom and One-to-One Massed Practice Instruction in the Special Education Classroom

Abstract: A single subject alternating treatment design was used to compare the relative effectiveness of one-to-one embedded instruction in the general education classroom and one-to-one massed practice instruction in a special education class. Four middle school students with developmental disabilities, their special education teacher, and paraprofessional participated in the study. The results indicate that embedded instruction is an effective instructional strategy for students with developmental disabilities being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 22 publications
2
55
0
Order By: Relevance
“…When used in general education contexts the use of distributed trials is called embedded instruction (McDonnell, Johnson, & McQuivey, 2008). Numerous studies have examined the use of embedded instruction to teach specific skills to students with severe disabilities (Jameson, McDonnell, Johnson, Riesen, & Polychronis, 2007;McDonnell, Johnson, Polychronis, & Riesen, 2002;Wolery et al, 2002). For example, Johnson and McDonnell (2004) examined the effects of teacher-delivered embedded instruction in a general education elementary classroom on core content with three students with moderate intellectual disability.…”
mentioning
confidence: 99%
“…When used in general education contexts the use of distributed trials is called embedded instruction (McDonnell, Johnson, & McQuivey, 2008). Numerous studies have examined the use of embedded instruction to teach specific skills to students with severe disabilities (Jameson, McDonnell, Johnson, Riesen, & Polychronis, 2007;McDonnell, Johnson, Polychronis, & Riesen, 2002;Wolery et al, 2002). For example, Johnson and McDonnell (2004) examined the effects of teacher-delivered embedded instruction in a general education elementary classroom on core content with three students with moderate intellectual disability.…”
mentioning
confidence: 99%
“…In addition, several studies have documented the application of systematic instruction as an evidence-based practice for teaching academic skills to children with disabilities (Morse & Schuster, 2004;Browder et al, 2009). In this systematic review, four studies applied systematic instruction as a strategy of teaching various academic skills to students with multiple disabilities (Jameson et al, 2007;Mechling, Gast, & Langone, 2002;Smith et al, 2011;Browder, Hudson & Wood, 2013). Jameson et al (2007) demonstrated that systematic instruction is also an evidence based practice where students are taught word and symbol recognition using differential reinforcement and constant time delay among students with moderate intellectual disabilities.…”
Section: First Research Questionmentioning
confidence: 99%
“…In this systematic review, four studies applied systematic instruction as a strategy of teaching various academic skills to students with multiple disabilities (Jameson et al, 2007;Mechling, Gast, & Langone, 2002;Smith et al, 2011;Browder, Hudson & Wood, 2013). Jameson et al (2007) demonstrated that systematic instruction is also an evidence based practice where students are taught word and symbol recognition using differential reinforcement and constant time delay among students with moderate intellectual disabilities. Similarly, Mechling, Gast, and Langone (2002) successfully applied video simulations in teaching students who had moderate intellectual disabilities the task analysis steps for tracing items within a grocery store.…”
Section: First Research Questionmentioning
confidence: 99%
“…Similarly, Jameson et al (2007) compared one-to-one embedded instruction in general education classes to one-toone massed practice instruction in a special education classroom. In each setting, special education teachers and paraprofessionals taught vocabulary definitions from tbe general curriculum using constant time delay, differential reinforcement, and error correction.…”
Section: Teaching Science Vocahularymentioning
confidence: 99%
“…In ELA, math, and science, gradealigned vocabulary and definitions can be taught using time delay (e.g., Jameson et al, 2007). Additionally, many chained tasks, such as completing the steps to composing a paragraph, completing a long division problem, or participating in an inquiry lesson can be taught using a task analysis of the steps.…”
Section: Summary Oe Academic Instruction In Ela Math and Sciencementioning
confidence: 99%